Ketahanan Ideologi Pancasila Dalam Menghadapi Distrupsi Revolusi Industri 4.0 - H.M Rifqinizamy Karsayuda; Rahmadi Indra Tektona (Universitas Gadjah Mada, 2021)
ABSTRACTThe era of disruption that occurred globally had affected all human life in various fields, both in the economic, social, cultural, political, educational and other fields. Disruption had a positive impact, but it would also have a negative impact if it was not treated wisely. Geostrategy could be used as an effort to maintained ideological resilience, which was one of the basic things needed in realizing national resilience.The research method used in this article was normative research; the research stage, literature study; and deductive analysis, the type of research approach used was the conceptual approach and the statutory approach. This study discussed Pancasila as the source of all sources of law as well as the ideology of Indonesia's geostrategic resilience in the face of an era of global disruption. The author also used the literature methodIn this era of global disruption, Pancasila as the basis of the state and the nation's outlook on life played an important role in being able to filtered new values, by applying Pancasila values in all aspects of national life so as to maintained national resilience while still paying attention to the existence of Indonesian geostrategy which had Pancasila as an ideology of geostrategic resilience which was a reflection of the existing values and lives of the precepts contained in it.ABSTRAKDistrupsi industri 4.0 telah mempengaruhi seluruh kehidupan manusia di berbagai bidang, baik di bidang ekonomi, sosial, budaya, politik, pendidikan, dan bidang lainnya. Memberikan dampak positif dan negatif jika tidak disikapi dengan bijak. Geostrategi dapat dimanfaatkan sebagai upaya menjaga ketahanan ideologi yang merupakan salah satu hal dasar yang diperlukan dalam mewujudkan ketahanan nasional.Metode penelitian yang digunakan dalam artikel ini adalah penelitian normatif; tahap penelitian, studi kepustakaan; dan analisis deduktif, jenis pendekatan penelitian yang digunakan adalah pendekatan konseptual dan pendekatan perundang-undangan. Penelitian ini membahas mengenai Pancasila sebagai sumber segala sumber hukum yang juga sebagai ideologi ketahanan geostrategi Indonesia dalam menghadapi era global. Peneliti juga menggunakan metode kepustakaan (library research).Dalam distrupsi industri 4.0, Pancasila sebagai dasar negara dan pandangan hidup bangsa memegang peranan penting untuk dapat menjadi filter nilai-nilai baru, dengan menerapkan nilai-nilai Pancasila dalam segala aspek kehidupan nasionalnya diharapkan mampu mempertahankan ketahanan nasional dengan tetap memperhatikan eksistensi geostrategi Indonesia.